The Use of Visual Presentation in Teaching English Vocabulary to Students with Special Needs at PKBM Zaien Education Centre - Riamin Elfrida; Lenny Solo; Syamsi Edi (Jurnal Ilmiah Literasi Indonesia, 2025)
This study is entitled "The Use of Visual Presentations in Teaching English Vocabulary to Special Needs Students at PKBM Zaien Education Centre." This research aims to determine the effectiveness of using visual media, such as flashcards and educational videos, in enhancing the English vocabulary skills of students with special needs, particularly in learning colors and facial features. This study employed a quasi-experimental approach with the Visual-Auditory-Kinaesthetic (VAK) learning method involving 15 students. The learning media used included videos and flashcards with themes of basic colors (blue, red, green, yellow) and facial parts (eyes, nose, mouth, ears). Assessments were conducted through three tests measuring students' ability to recognize and pronounce the taught vocabulary. The results showed a significant improvement in students' vocabulary skills after using visual media. In the second cycle, 12 out of 15 students achieved passing scores (Minimum Mastery Criteria ≥ 9), an increase compared to the first cycle, where only 6 students passed. This indicates that the use of visual presentations can help special needs students better understand and remember English vocabulary. Therefore, the use of visual media is highly recommended in teaching English to special needs students to enhance learning effectiveness, inclusivity, and responsiveness to individual student needs.